Sleep Deprivation Related Changes of Plasma Oxytocin in Males and Female Contraceptive Users Depend on Sex and Correlate Differentially With Anxiety and Pain Hypersensitivity - Schuh-Hofer, Sigrid; Eichhorn, Nicole; Grinevich, Valery; Treede, Rolf-Detlef (Frontiers in Behavioral Neuroscience, 2018)
Disturbed sleep is known to substantially aggravate both the pain condition and the affective state of pain patients. The neurobiological mechanisms underlying these adverse effects are unknown. Oxytocin (OT), being largely involved in social and emotional behavior, is considered to also play a modulatory role in nociception. We hypothesized a pathophysiological role of OT for the hyperalgesic and anxiogenic effects of sleep loss. An established human model of one night of total sleep deprivation (TSD) was used to test this hypothesis. Twenty young healthy students (n=10 male, n=10 female) were investigated in a balanced cross-over design, contrasting TSD with a night of habitual sleep (HS). All females took monophasic oral contraceptives (OC) and were investigated during their 'pill-free' phase. Plasma OT concentrations were correlated with 1) pain thresholds, 2) descending pain inhibition, and 3) state-anxiety scores. Compared to the HS condition, the plasma OT concentration was significantly increased in sleep deprived females (p=0.02) but not males (p=0.69). TSD resulted in pain hypersensitivity to noxious cold (p=0.05), noxious heat (p=0.023) and pricking stimuli (p=0.013) and significantly increased state-anxiety (p=0.021). While, independent of sex, lower heat pain thresholds correlated with higher plasma OT (p=0.036), no such associations were found for cold/mechanical pain. In sleep-deprived females, higher plasma OT showed a mild (but insignificant) association with lower pain inhibition (p=0.093). We found a positive correlation between anxiety-scores and OT (p=0.021), which was enhanced when respecting ‘sex’ (p=0.008) and ‘sleep’ (p=0.001) in a hierarchical regression analysis. Altogether, our study revealed a complex and partially sex-dependent correlation between plasma OT and TSD-induced changes of experimental pain and anxiety. The minor role of OT for TSD-induced changes of evoked pain, and its major involvement in anxiety, argues against a specific role of OT for linking the adverse effects of TSD on pain sensitivity and anxiety with each other. Future investigations are needed in order to dissect out the effect of oral contraceptives on the sex-dependent effects of TSD observed in our study.